Web-based New Student Admission Information System at Daycare and Pre School Ananda Mandiri Slawi - Amanda, Yuliah; Galih Widyatmojo; Mutiara Handayani Ujianti (LPPM STIKOM Dinamika Bangsa, 2026)
Pre-school education, often referred to as Early Childhood Education (ECED), aims to support children's physical, emotional, social and cognitive development through various fun learning activities. The recording system for the admission of new students at Ananda Mandiri Slawi Daycare and Pre School is still done conventionally, the committee records data into a ledger and submits it to the Principal once a month. The registration form contains the initial information of prospective participants, which is then recorded in the ledger as an official record and administrative reference. However, this process often experiences problems because registration forms and required files are often scattered, coupled with limited storage space. The problem to be investigated is how the information system for the acceptance of new students based on the web at Daycare and Pre School Ananda Mandiri Slawi. This research methodology uses data collection methods, namely observation methods, interview methods, library research. The design method used is the Unified Model Language (UML) method through several stages, namely making use cases diagrams, making activity diagrams, making sequence diagrams, and making class diagrams. The parties involved in registration are prospective participants, student guardians, committees, and school principals. The results obtained are registration data and payment data..